Combustion Activation Induced Solid‐State Synthesis for N, B Co‐Doped Carbon/Zinc Borate Anode with a Boosting of Sodium Storage Performance - Hao Zhang; Dingyue Zhang; Mingyi Guo; Zheng Huang; Xu Wang; Caiqin Gao; Fan Gao; Mauricio Terrones; Yanqing Wang (Advanced Science)
Abstract Zinc borates have merits of low voltage polarization and suitable redox potential, but usually suffer from low rate capability and poor cycling life, as an emerging anode candidate for Na+ storage. Here, a new intercalator‐guided synthesis strategy is reported to simultaneously improve rate capability and stabilize cycling life of N, B co‐doped carbon/zinc borates (CBZG). The strategy relies on a uniform dispersion of precursors and simultaneously stimulated combustion activation and solid‐state reactions capable of scalable preparation. The Na+ storage mechanism of CBZG is studied: 1) ex situ XRD and XPS demonstrate two‐step reaction sequence of Na+ storage: Zn6O(OH)(BO3)3+Na++e−↔3ZnO+Zn3B2O6+NaBO2+0.5H2 ①, Zn3B2O6+6Na++6e−↔3Zn+3Na2O+B2O3 ②; reaction ① is irreversible in ether‐based electrolyte while reversible in ester‐based electrolyte. 2) Electrochemical kinetics reveal that ether‐based electrolyte possesses faster Na+ storage than ester‐based electrolyte. The composite demonstrates an excellent capacity of 437.4 mAh g−1 in a half‐cell, together with application potential in full cells (discharge capacity of 440.1 mAh g−1 and stable cycle performance of 2000 cycles at 5 A g−1). These studies will undoubtedly provide an avenue for developing novel synthetic methods of carbon‐based borates and give new insights into the mechanism of Na+ storage in ether‐based electrolyte for the desirable sodium storage.